2018
DOI: 10.1111/jocd.12516
|View full text |Cite
|
Sign up to set email alerts
|

IL1A (‐889) gene polymorphism is associated with the effect of diet as a risk factor in Acne Vulgaris

Abstract: IL-1A (-889) gene polymorphism has a role in the pathogenesis of acne vulgaris. We suggest that the triggering or exacerbating effect of diet on acne may be related to IL-1A (-889) gene polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(30 reference statements)
0
10
0
1
Order By: Relevance
“…Both "hair loss" and "acne" may be associated with emotional stress. [20][21][22][23][24] "Hair loss" search term was at the highest point in the second month of the COVID-19 pandemic in Turkey. Of note, this result may indicate that the short term (<2 months) is more important than the long term in the context of stress period for hair loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both "hair loss" and "acne" may be associated with emotional stress. [20][21][22][23][24] "Hair loss" search term was at the highest point in the second month of the COVID-19 pandemic in Turkey. Of note, this result may indicate that the short term (<2 months) is more important than the long term in the context of stress period for hair loss.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that “hair loss” and “acne” search terms were increased in both countries in April and May 2020. Both “hair loss” and “acne” may be associated with emotional stress 20‐24 . “Hair loss” search term was at the highest point in the second month of the COVID‐19 pandemic in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…30 La severidad del acné en la adolescencia es más común a mayor edad, raza blanca, género femenino y mejor nivel socioeconómico. 31 Dentro de los factores de riesgo de acné moderado/severo se encuentran: antecedentes familiares (polimorfismo genético IL-1A -889 entre otros), 32 índice de masa corporal mayor de 23 Kg/m 2 , consumo de leche, inicio temprano de acné comedonal, altos niveles séricos de hormona dehidroepiandrosterona sulfato (DHEAS), 25,28 y el contenido y composición de los lípidos de la superficie de la piel. 33 La oclusión de la superficie de la piel con productos grasosos, la ropa y la sudoración pueden empeorar el acné.…”
Section: Epidemiologíaunclassified
“…Acne vulgaris is a multifactorial inflammatory skin condition resulting from the integration between multiple factors including androgen‐induced increase in sebum secretion, altered keratinization, inflammation, pilosebaceous unit colonization by Cutibacterium acnes ( C . acnes ), delayed‐type immune reaction, diet, and genetic factors 1 …”
Section: Introductionmentioning
confidence: 99%
“…
Acne vulgaris is a multifactorial inflammatory skin condition resulting from the integration between multiple factors including androgeninduced increase in sebum secretion, altered keratinization, inflammation, pilosebaceous unit colonization by Cutibacterium acnes (C. acnes), delayed-type immune reaction, diet, and genetic factors. 1 The proteolytic enzymes, matrix metalloproteinases (MMPs) and intrinsic tissue inhibitors of metalloproteinases (TIMPs), regulate extracellular matrix (ECM) remodeling and inflammatory signaling.
…”
mentioning
confidence: 99%